2021
DOI: 10.1159/000518879
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Ischemia-Reperfusion Injury: Therapeutics from a Mitochondria-Centric Perspective

Abstract: Coronary arterial disease is the most common cardiovascular disease. Myocardial ischemia-reperfusion injury caused by the initial interruption of organ blood flow and subsequent restoration of organ blood flow is an important clinical problem with various cardiac reperfusion strategies after acute myocardial infarction. Even though blood flow recovery is necessary for oxygen and nutrient supply, reperfusion causes pathological sequelae that lead to the aggravation of ischemic injury. At present, although it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 90 publications
0
38
0
Order By: Relevance
“…Mitochondrial dysfunction is a key feature of IR injury [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ], and the pan-inhibition of δPKC, with δV1-1, prevents IR-induced increases in mitochondrial oxidant production, and decreases in ATP levels [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. However, the mechanism by which δPKC causes mitochondrial dysfunction, and the protein substrate that mediates it, have not been identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial dysfunction is a key feature of IR injury [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ], and the pan-inhibition of δPKC, with δV1-1, prevents IR-induced increases in mitochondrial oxidant production, and decreases in ATP levels [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. However, the mechanism by which δPKC causes mitochondrial dysfunction, and the protein substrate that mediates it, have not been identified.…”
Section: Resultsmentioning
confidence: 99%
“…An IR event leads to critical changes in mitochondrial function, bioenergetics, and redox balance in the cardiomyocyte [ 18 , 37 ]. These mitochondrial changes result in cell death, tissue remodeling, and contractile dysfunction [ 21 ]. Here, we measured the rates of oxygen consumption and production of the oxidant species H 2 O 2 from isolated cardiac mitochondria after IR.…”
Section: Discussionmentioning
confidence: 99%
“…These findings imply that HJ11 decoction alleviated myocardial I/R injury by suppressing ACSL4-mediated ferroptosis. It is well known that apoptosis and ferroptosis are two different forms of cell death ( Zhou et al, 2021 ). This study revealed that HJ11 decoction attenuated apoptosis and ferroptosis in the myocardial tissues of myocardial I/R injury rats.…”
Section: Discussionmentioning
confidence: 99%
“…There are several sources of ROS during myocardial I/R injury, including the mitochondrial electron transport chain (ETC) [ 9 , 10 , 11 ], xanthine oxidase [ 12 , 13 ], and Noxs [ 2 , 14 , 15 ]. Of these, Noxs are major contributors to ROS production during myocardial I/R injury [ 16 ].…”
Section: Oxidative Stress and Myocardial I/r Injurymentioning
confidence: 99%